Perancangan Bisnis Manajemen Media Sosial yang Berbasis Infografis - Tavia Angelica; Rendy Iswanto (Jurnal Vicidi, 2019)
With the development of startup businesses, the use of social media such as Instagram became something essential for startups to have as a promotional media and this is an opportunity for social media management services to grow as well. Social media services open an opportunity to use a variety of designs to maximize the view of social media such as infographics. Infographics are visualization of data or information into a visual graphic to make it easier for readers to absorb information. The process of making an infographic starts with research, accumulation and processing of linear or written data to simplified visual data. The goal of this research is to know if infographics can be used as one of the design forms of social media marketing services for startup businesses. The method that will be used for this research is primary data. The results of the research show that most of the respondents are already aware of social media management services and they think that the use of infographics as the base design of social media management is interesting.